Repetition of Spiritual Mantra Meditation: A Review - Rozeeda Kadri (Fakulti Pengajian Islam, Universiti Malaysia Sabah, 2023)
Introduction: Studies on spiritual mantra meditation represent a growing field. Objectives: This review paper aims on several repetition of spiritual mantra meditation including the practices and its effect on health. Methods: The selected papers were searched by using PubMed and Scopus databases from 2007-2017. The terms used were ‘mantra’, ‘chanting’, ‘religious chanting’, ‘zikr’ or ‘dhikr’ and other relevant terms. Result: Twenty six original papers consist of several spiritual mantra meditations were identified; OM chanting, Gayatri mantra, Dhikr (remembrance of Allah), Kirtan Kriya and Mantram Repetition Program (MRP). The vast majority of studies were quantitative intervention study, 4 observational studies, 2 comparative study and qualitative study and a case study. Among the 26 papers that met the criteria, 84 percent (%) papers gave positive results on the outcomes in various domains and 12% and 4% are not shown particular result and mix results respectively. Discussion: New mantra meditation such as MRP and dhikr were found in this review. The participant covered for this study majority from healthy individuals, cancer patient, Post Traumatic Syndrome Disorder (PTSD), chronic kidney Disease (CKD) and patient undergoing coronary artery bypass graft surgery. However, a definite conclusion cannot be drawn. Conclusion: Spiritual mantra meditation has positive impact in physical and mental health. Future study on the ability and feasibility of repetition of spiritual mantra meditation need to be explored.